Medication use patterns and polypharmacy among elderly in Iran: a cross-sectional study using national health insurance claims data - Sepehr Khosravi; Mohammad Reza Amini; Mohammad-Reza Malekpour; Zahra Shahali; Seyed Mohammad-Navid Ataei; Ali Golestani; Ozra Tabatabaei-Malazy; Mahbube Ebrahimpur; Fatemeh Sadat Mirzadeh; Mohammad Effatpanah (BMJ Open)
Objectives Polypharmacy, defined as the concurrent use of multiple medications, is a growing concern among the elderly, especially in low-income and middle-income countries such as Iran. This study aims to explore the prevalence and patterns of polypharmacy among the elderly in Iran, using health insurance claims data to identify common drug classes and coprescribed medications, with a focus on informing policy decisions and improving medication management.Design Retrospective population-based observational study.Setting Nationwide data from the Iran Health Insurance Organization (IHIO) across 24 provinces.Participants 1 876 527 individuals aged 65 years and older, insured by the IHIO from 2014 to 2017. Individuals with incomplete demographic information or lacking medication records in the database were excluded from the analysis.Primary and secondary outcome measures Prevalence and patterns of polypharmacy, demographic factors associated with polypharmacy, and common drug classes used. Medications were classified using the Anatomical Therapeutic Chemical system. Polypharmacy was defined as the use of five or more medications, with cumulative polypharmacy considering total drug use over time, and consecutive polypharmacy focusing on the frequency of monthly drug use. Logistic regression and association rule mining were applied to explore demographic factors and medication patterns associated with polypharmacy.Results Of the study population, 74.9% experienced cumulative polypharmacy over 6 months and 64.6% over 1 month, with 7.6% experiencing consecutive polypharmacy. Females and those aged 75–79 were more prone to polypharmacy. Systemic glucocorticoids were the most commonly used medications (50.02%), followed by HMG-CoA reductase inhibitors (42.73%) and platelet aggregation inhibitors (41.92%). Polypharmacy was most strongly associated with medications related to the alimentary tract and metabolism, cardiovascular system, nervous system and blood and blood-forming organs.Conclusions Polypharmacy is highly prevalent among the elderly in Iran, with significant variations by gender, age, insurance fund and region. The findings highlight the need for targeted interventions to manage polypharmacy and improve medication safety in this population.